Strategi Pemasaran Pembiayaan KPR di Bank Syariah Indonesia Kantor Cabang Pembantu Mojosari Pada Masa Pandemi Covid-19 - Syafar, Aldisar; Mukhlisuddin, Ahmad; Aftian, Rahman Yusri (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This study aims to analyze the marketing strategy of mortgage financing (KPR - Home Ownership) implemented by Bank Syariah Indonesia Sub-Branch Office Mojosari during the COVID-19 pandemic. The research method used is qualitative descriptive with a field research approach. Data was collected through in-depth interviews with the Unit Head and Account Officer of BSI KCP Mojosari, observation, and documentation. The results showed that BSI KCP Mojosari implemented a marketing mix strategy that was not much different from the pre-pandemic period, but with a significant increase in the promotional aspect through social media such as WhatsApp, Facebook, and Instagram. The use of digital media helped banks maintain and increase marketing activities without violating health protocols. The impact of this strategy can be seen from the increase in the number of mortgage customers from 10 people in 2019 to 20 people in 2020-2021. This research contributes to understanding the adaptation of Islamic banking marketing strategies in facing pandemic challenges.